AN EMPIRICAL INVESTIGATION OF EXPORT COMPETITIVENESS OF PAKISTAN’S MEAT SECTOR - M. B. Naeem; S. Naveed; S. E. Samma; A. Nazuk (Journal of Animal and Plant Sciences, 2022)
This study attempts to explore the export potential and competitive position of Pakistan’s meat sector versus the World’s leading meat exporters using RCA scores of 26 meat products lines at HS 6-digit code from 2009-2018. The study also explores the untapped Halal Meat export potential for UAE and Saudi Arabia by using indicative trade potential. The findings of the study reveal that Pakistan possesses strong comparative advantage in low value-added bovine meat products while has a weak comparative advantage in high value-added categories of the same product line against its leading competitors like Brazil, USA, Netherlands and Australia. Poultry comes out to be an emerging sub sector, while the meat of goat, lamb and sheep witnessed a decreasing RCA score post 2013 and are categorized as the threatened products. The untapped Halal meat export potential to Saudi Arabia and UAE comes out to be worth $ 132 million. To become a global market player in high value-added meat products and to realize untapped export potential, Pakistan needs to address the issues of traceability, weak supply chains, insufficient number of local meat brands, weak infrastructure, improperly managed marketing strategies, noncompliance to international standards, and halal meat certifications.
Keywords: Meat; Exports; RCA; Comparative Advantage; Indicative Trade Potential